Bargaining under Time Pressure - Emin Karagözoglu; Martin G. Kocher (Center for Economic Studies and ifo Institute (CESifo), 2015)
We experimentally investigate the effect of time pressure in a rich-context, unstructured bargaining game with earned status and competing reference points. Our results show that average opening proposals, concessions, and agreed shares are very similar across different levels of time pressure. Nevertheless, as predicted, time pressure systematically influenced agreements. In particular, the likelihood of bargainers reaching the explicit reference point outcome in agreements increases with time pressure, and the likelihood of reaching the implicit reference point (equal division) in agreements decreases with time pressure. Disagreement rates and the frequency of last-moment agreements are strongly affected: the disagreement rate rises dramatically with time pressure, and last-moment agreements are significantly more frequent. This effect is explained by a stronger connection between the tension in first proposals and the final bargaining outcome under time pressure than without time pressure.
Keywords: C71; C91; D74; 330; bargaining; disagreements; last-moment agreements; reference points; time pressure